Academic Senate Minutes 2005-12-15 - Academic Senate:::::::::
Chair's Report. Agenda amended and approved. Minutes of 12/1/05 approved. CCJ Electives and Sociology Curriculum changes approved. Course Repeat Policy approved. Course Add Policy approved. Update on WASC. Special Report – Update on First Year Experience – S. Von Meier. Discussion of Funding Plan for Program Review. Motion that plan in packet regarding Program Review satisfies previous Senate resolution – approved. Provost report. Vice President of Administration and Finance report. Good of the Order.